KUALITAS PELAYANAN PADA OBJEK WISATA BOOMBARA WATERPARK PASIR PUTIH KABUPATEN KAMPAR - Rosita Royda; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this research is how the quality of service at waterpark boombara tourism objek pasir putiht distric Kampar background of the research his to findout the service provide by tourism attraction to consumers. Thi is important as a references to revam the service quality in order to passably.This research was used descriptive quantitatifmethod to describe the issues. The sample used in this research was 7 people. Quesionnaires, interviews, and observations were used to collect the research data.The results of this research indicate that based on the research results obtained on the employee job the quality of service at waterpark boombara tourism objek pasir putiht distric Kampar quite passably..This is evidenced by the acquisition of the overall total score, which is 264 points. the quality of service at waterpark boombara tourism objek pasir putiht distric Kampar town in each variable, responsivenes, and assurance was rated passable. While emphaty, realibility , and tangible variable were rated good.Keywords: Quality, Service waterpark boombara